Study guide : HBEC3403 creativity in early childhood - Badzis, Mastura; Abdullah, Nor Faizah (Open University Malaysai (OUM), 2012)
This course is designed to enable you to explore the importance of creativity and creative arts such as visual arts, music, drama, and movement in early childhood education. The theories and models that relate to young children’s creative development will be examined. You also learn to design an environment that matches children’s unique and creative ways of learning that inspire them to use their intelligence, think in creative ways, work together and make connections across content areas.